The concept of criticism in the “Generación del 98” - Rivas Hernández, Ascensión (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
Some writers of the so called “Generación del 98” (Unamuno, Machado and Baroja) focus their reflections on literary criticism: concept, finality, achievements, errors... And, unlike realist writers, they do their criticism in non academic works. Their own activities as literary authors placed them in an outstanding position in order to judge how their works were received; so, they do criticism on literary criticism. Since they worked at the same time as writers and Critics, they were able to understand the difficulty of a good criticism. Also this double condition helped them to reflect on criticism with very sound arguments. This paper also reveals the modernity of Azorin, who is considered as the precursor of Reception Aesthetics.